2011
DOI: 10.1186/1749-8104-6-23
|View full text |Cite
|
Sign up to set email alerts
|

En1 and Wnt signaling in midbrain dopaminergic neuronal development

Abstract: Dopaminergic neurons of the ventral mesodiencephalon are affected in significant health disorders such as Parkinson's disease, schizophrenia, and addiction. The ultimate goal of current research endeavors is to improve the clinical treatment of such disorders, such as providing a protocol for cell replacement therapy in Parkinson's disease that will successfully promote the specific differentiation of a stem cell into a dopaminergic neuronal phenotype. Decades of research on the developmental mechanisms of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(63 citation statements)
references
References 191 publications
(235 reference statements)
1
60
0
Order By: Relevance
“…Conditional deletion of β-catenin mimics these defects [85,86], LRP6 mutants partially mimic the Wnt1 mutant phenotype [57], and Fzd3/Fzd6 double mutants also display disruptions in midbrain development [87]. Moreover, several studies, including LRP6 mutant analysis, overexpression of β-catenin, and ablation of β-catenin support a requirement for Wnt/β-catenin signaling in neurogenesis of midbrain dopaminergic neurons in the mouse [88,89,90,91]. …”
Section: Brain Regionalizationmentioning
confidence: 99%
“…Conditional deletion of β-catenin mimics these defects [85,86], LRP6 mutants partially mimic the Wnt1 mutant phenotype [57], and Fzd3/Fzd6 double mutants also display disruptions in midbrain development [87]. Moreover, several studies, including LRP6 mutant analysis, overexpression of β-catenin, and ablation of β-catenin support a requirement for Wnt/β-catenin signaling in neurogenesis of midbrain dopaminergic neurons in the mouse [88,89,90,91]. …”
Section: Brain Regionalizationmentioning
confidence: 99%
“…Engrailed 1 (En1) is known to be expressed in the midbrain beginning at about embryonic day (E) 8.0 (Chi et al, 2003;Davis and Joyner, 1988) and encompasses the majority of the DA primordium, excluding a small number of Th + neurons at the rostral-most extent (Lahti et al, 2012). Engrailed 1 and 2 (En1/2) are important for DA neuron generation and survival (Alberi et al, 2004;Alvarez-Fischer et al, 2011;Alves dos Santos and Smidt, 2011;Ellisor et al, 2012;Nordström et al, 2015;Rekaik et al, 2015;Simon et al, 2001;Veenvliet et al, 2013). Moreover, engrailed proteins are involved in various boundary formation systems such as the diencephalic-dorsal midbrain boundary (Matsunaga et al, 2000;Scholpp et al, 2003) and a D-V boundary in the limb apical ectodermal ridge (Kimmel et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…It was noticed that some known and required pathways for induction and formation of DA neurons were activated in 3D, including Wnt, SHH, MAPK and PD pathways. Wnt signalling pathway has been reported widely to control diverse processes such as cell proliferation, selfrenewal, cell polarity, cell death and cell fate specification [13]. The data has shown significant up-regulation of Wnt signaling genes in 3D such as WNT7B, WNT7A and FZD3.…”
Section: Discussionmentioning
confidence: 65%
“…The data has shown significant up-regulation of Wnt signaling genes in 3D such as WNT7B, WNT7A and FZD3. WNT7B and WNT7A have been shown to be involved in several developmental processes, including regulation of cell fate and patterning during embryogenesis [13][14][15]. The gene FZD3 has previously been reported that mutant mice with defects in frizzled family receptors such as FZD3 showed a severe impairment of midbrain morphogenesis [13,16].…”
Section: Discussionmentioning
confidence: 99%